Data on Smoking Across Three Generations Increase Both Smoking Prevention and Cessation - Igić, Rajko (Scripta Medica, 2024)
There is an association between grandparent (G1), parent (G2) and child (G3) on smoking behavior. The transmission of smoking behavior from one generation to the next takes place not only through genetics, but also by environmental influences. When smokers and non-smokers realize what factors contributed to smoking, this knowledge increases motivation for both prevention and quitting.